Educational Transformation in Islamic Higher Education in Response to Global Challenges - Muhammad Usaid; Donatella Camedda; Ita Tryas Nur Rochbani (Zabags International Journal of Education, 2026)
This study aims to a civilization that is already familiar with information and communication technology (ICT) is known as "society era 5.0." Students must develop a variety of abilities, such as critical thinking, creativity, inventiveness, teamwork, and communication. It is also necessary to strengthen character education, which tries to develop moral qualities (character) that set morals apart as a distinctive value. The method is a qualitative approach with a descriptive strategy to write this article. To do this, primary and secondary data are gathered, and descriptive analysis is performed to describe the facts as they appear both theoretically and empirically. Whereas primary and secondary data can be found in books, journals, articles, papers downloaded from the internet, online newspapers, and other source materials. The goal of this research is to identify the best approach for enhancing students' character education. This study also attempts to explain why character education is so important in the face of society 5.0. Descriptive qualitative methodology is applied, along with literature reviews. The study's findings demonstrate the value of character education in preparing pupils for the future. Information technology is used in character education to help students develop not only morality but also ICT proficiency and the ability to think creatively and innovatively in order to face today's society. 5.0.